Ebola, entre science et fiction - Frédéric Keck (Anthropologie & Santé)
This article examines the introduction of fiction in the management of emerging infectious diseases such as Ebola. Two modalities are distinguished to explain the use of fiction in the preparation of catastrophic epidemics whose probability cannot be calculated. In the imaginary of mutant viruses, fiction represents spaces of impurity through narratives of contagion, aiming at containing the disease. In the imaginary of viruses as enemies, fiction represents interactions between beings endowed with intentions on different scales, and helps to cope with the uncertainties of these interactions. Drawing on the anthropology of figuration, this article shows that these two modalities can be described through the opposition between an analogical ontology, anchored in pastoral practices, and an animistic ontology, anchored in cynegetic practices. This questions the role of images of « virus hunters » in the contemporary management of epidemics.